BIRTHDAY CAKE ACTIVITY STRUCTURED ARRANGEMENT FOR HELPING CHILDREN DETERMINING QUANTITIES - Mariana, Neni (Journal on Mathematics Education, 2010)
Few researches have been concerned about relation between children’s spatialthinking and number sense. Narrowing for this small research, we focused onone component of spatial thinking, that is structuring objects, and onecomponent of number senses, that is cardinality by determining quantities. Thisstudy focused on a design research that was conducted in Indonesia in which weinvestigated pre-school children’s (between 2 and 3.5 years old) ability inmaking structured arrangement and their ability to determine the quantities bylooking at the arrangements. The result shows us that some of the children wereable to make such arrangement. However, the children found difficulties eitherto determine quantities from those arrangements or to compare some structuresto easily recognize number of objects.